Pretreatment of macroalgal biomass for biogas production. (15th January 2016) - Montingelli, M.E.; Benyounis, K.Y.; Stokes, J.; Olabi, A.G.
Highlights: The beating pretreatment speeds up the start of digestion. After 3 days of digestion, beating pretreatment enhances the methane yield by 37%. Microwave and ball milling pretreatment impacts negatively on methane production. At 25 days of digestion the overall methane is not enhanced by beating pretreatment. Abstract: The objective of this study was to evaluate the effect of beating (BT), ball milling (BM) and microwave pretreatment (MW) on the conversion of the macroalgae Laminaria spp . into biogas by anaerobic digestion (AD). The AD was carried out in batch at 38 ± 1 °C, over an incubation time of 25 days. After 3 days of digestion the BT pretreated samples yielded the best result by achieving a methane increase of up to 37% with respect to the raw seaweed. At 25 days, both BM and MW pretreatment lowered the methane yield with respect to the raw seaweed. Since BT produced higher methane yields with respect to the untreated sample, it was considered for energy balance analysis. After 3 days of digestion, the BT resulted in an energy gain of 28%, while at the end of digestion the break-even point was reached.